Comparison of the Safety of Seven Iodinated Contrast Media - Seong, Jong-Mi; Choi, Nam-Kyong; Lee, Joongyub; Chang, Yoosoo; Kim, Ye-Jee; Yang, Bo Ram; Jin, Xue-Mei; Kim, Ju-Young; Park, Byung-Joo (Journal of Korean medical science, 2013)
We aimed to determine the characteristic adverse events (AEs) of iodinated contrast media (IOCM) and to compare the safety profiles of different IOCM. This study used the database of AEs reports submitted by healthcare professionals from 15 Regional Pharmacovigilance Centers between June 24, 2009 and December 31, 2010 in Korea. All reports of IOCM, including iopromide, iohexol, iopamidol, iomeprol, ioversol, iobitridol and iodixanol, were analyzed. Safety profiles were compared between different IOCM at the system organ level using the proportional reporting ratio (PRR) and 95% confidence interval (95% CI). Among a total of 48,261 reports, 6,524 (13.5%) reports were related to the use of IOCM. Iopromide (45.5%), iohexol (16.9%), iopamidol (14.3%) and iomeprol (10.3%) were identified as frequently reported media. 'Platelet, bleeding & clotting disorders' (PRR, 29.6; 95%CI, 1.9-472.6) and 'urinary system disorders' (PRR, 22.3; 95% CI, 17.1-29.1) were more frequently reported for iodixanol than the other IOCM. In conclusion, the frequency of AEs by organ class was significantly different between individual media. These differences among different IOCM should be considered when selecting a medium among various IOCM and when monitoring patients during and after its use to ensure optimum usage and patient safety.